1982
DOI: 10.1159/000233108
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Salivary IgA Levels in Normal Subjects: Comparison between Tonsillectomized and Non-Tonsillectomized Subjects

Abstract: Serum IgA and secretory IgA (SIgA) were determined in 1,000 apparently healthy subjects; 274 were tonsillectomized. Four groups were identified in this study: (1) 0.3% of subjects had no serum IgA and SIgA; (2) 1.6% of subjects showed partial serum and SIgA deficiency; (3) 27.4% of individuals were tonsillectomized and had partial serum IgA deficiency but normal SIgA, and (4) 71.4% were normal, both with respect to serum IgA and SIgA. These results stress the relatively high incidence of IgA deficiency in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 13 publications
0
29
1
Order By: Relevance
“…In 1982, D'Amelio et al (4) found that the serum IgA was significantly lower in tonsillectomized patients compared to controls. However, there were no preoperative values to compare with.…”
Section: Discussionmentioning
confidence: 99%
“…In 1982, D'Amelio et al (4) found that the serum IgA was significantly lower in tonsillectomized patients compared to controls. However, there were no preoperative values to compare with.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical sequalae of that decrease was not clear. In the largest of these studies (D'Amelio et al [11], 274 patients) the clinical relevance was not studied and in the 2 nd large study (Böck A et al [22], 160 patients) the results were clinically insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…We could not isolate the data of the pediatric patients from those of adults within each of these articles, so we kept them combined and pointed to any reported difference in results within each article, where applicable. Another reason we did not exclude these studies is the fact that some included different age groups for comparison which was quite useful [8,10,25], while others looked at the sequalae of tonsillectomy in young adults who had tonsillectomy in the past [11]. The timing of postoperative testing varied from 10 days to 11 years, with 2 studies not specifying the timing.…”
Section: Page 6 Of 29mentioning
confidence: 99%
“…One of the first reports on immune system impact by Ogra showed that adenotonsillectomy in children reduces the level of IgA antibody to poliovirus approximately fourfold and subsequently delays local immune response to subsequent live oral poliovaccine [17]. Later studies have also validated a decrease in IgA levels [18][19][20]. Other studies have suggested that IgG levels are significantly decreased following adenotonsillar surgery [21][22][23].…”
Section: Discussionmentioning
confidence: 99%